THE EFFECTS OF TEACHING METHOD AND EMOTIONAL INTELLIGENCE UPON STUDENT’S SPEAKING SKILL - Budi Hartono (Premise: Journal of English Education and Applied Linguistics, 2016)
This study aims to determine the effects of teaching method and emotionalintelligence upon student’s speaking skill at the private vocational school in east Lampung. Research hypothesis included: 1) there is effect of teachingmethod upon student’s speaking skill, 2) there is effect emotionalintelligence upon student’s speaking skill, 3), there is interaction betweenteaching method and emotional intelligence upon student’s speaking skill.Method used in this research in experimental method. The population is allstudents and the sample of 40 students who obtained a random samplingtechnique that use cluster sampling. Instrument that is used is result test ofstudent’s speaking skill in the multiple choice with 35 items that is testedvalidity with reliability coefisient = 0,82, questionnaire 38 items ofemotional intelligence that is tested validity with reliability coefficient = 0,72. Analysis of data uses analysis of variance (ANOVA) two-ways. Resultof the rsearch show that there sre effects of teaching method and emotiona lintelligence upon studnt’s speaking skill.